Job loss at home: Children's school performance during the Great Recession - Jenifer Ruiz-Valenzuela (SERIEs - Journal of the Spanish Economic Association, 2020)
This paper studies the intergenerational impact of parental job loss on school performance during the Great Recession in Spain. Collecting data through parental surveys in a school in the province of Barcelona, I obtain information about the parental labour market status before and after the Great Recession. I can then link this information to repeated information on their children's school performance, for a sample of over 300 students. Using individual fixed effects, the estimates show a negative and significant decrease on average grades of around 15% of a standard deviation after father's job loss. These results are mainly driven by those students whose fathers suffer long unemployment spells. In contrast, the average impact of mother's job loss on school performance is close to zero and non-significant. The decline in school performance during the Great Recession after father's job loss, particularly among disadvantaged students, could result in detrimental long-term effects that might contribute to increased inequality. This could be an important and underemphasised cost of recessions.
Keywords: I20; I24; J63; J65; 330; Parental job loss; School performance; Great Recession